The Effect of Using the Fixed and Variable Exercise Scheduling on Developing Some Basic Volleyball Skills - Ahmed Al- Al-sweede (College of Physical Education and Sport Sciences, 2021)
The research aims to: 1. Investigating the effect of using the fixed and variable training methods in developing some basic volleyball skills. 2. Comparing the effect of using the fixed and variable training methods in developing some basic volleyball skills in the post test. The researcher used the experimental approach to its suitability and the nature of the research, the research sample consisted of (16) students, after students and they were expelled from  the performance of the tests, thus, the sample was divided into two experimental groups equal in number and by (8) students for each group. Homogeneity and parity were also performed in growth variables, some physical and motor variables, and some basic volleyball skills. The educational programs included (20) educational units distributed among the two research groups and by (10) educational units for each group, and the implementation of each educational program took five weeks, during which educational units were distributed at the rate of (2) educational units per week for each group, and the educational unit time was and for both methods (90) minutes. The data was statistically processed using the statistical program (SPSS). The researcher concluded the following: 1. The variable exercise method used by the first experimental group had a positive effect in developing all the basic skills of volleyball (under discussion). 2. The static training method used by the second experimental group had a positive effect in developing the basic skills of volleyball (sending, receiving, blocking wall) and did not develop the skills (passing and crushing). 3. The variable exercise method used by the first experimental group outperformed the static exercise method that the second experimental group used to develop all basic volleyball skills (under consideration).